Self-Serving Episodic Memory Biases: Findings in the Repressive Coping Style - Alston, Lauren L.; Kratchmer, Carissa; Jeznach, Anna; Bartlett, Nathan T.; Davidson, Patrick S.; Fujiwara, Esther (Frontiers in Behavioral Neuroscience, 2013)
Individuals with a repressive coping style self-report low anxiety, but show high defensiveness and high physiological arousal. Repressors have impoverished negative autobiographical memories and are better able to suppress memory for negatively valenced and self-related laboratory materials when asked to do so. Research on spontaneous forgetting of negative information in repressors suggests that they show significant forgetting of negative items, but only after a delay. Unknown is whether increased forgetting after a delay is potentiated by self-relevance. Here we asked in three experiments whether repressors would show reduced episodic memories for negative self-relevant information when tested immediately versus after a 2-day delay. We predicted that repressors would show an exaggerated reduction in recall of negative self-relevant memories after a delay, at least without anew priming of this information. We tested a total of 300 participants (experiment 1: N= 95, experiment 2: N=106; experiment 3: N=99) of four types: repressors, high anxious, low anxious, and defensive high anxious individuals. Participants judged positive and negative adjectives with regard to self-descriptiveness, serving as incidental encoding. Surprise free recall was conducted immediately after encoding (experiment 1), after a 2-day delay (experiment 2) or after a 2-day delay following priming via a lexical decision task (experiment 3). In experiment 1, repressors showed a bias against negative self-relevant words in immediate recall. Such a bias was neither observed in delayed recall without priming nor in delayed recall with priming. Thus, counter to our hypothesis, negative information that was initially judged as self-relevant was not forgotten at a higher rate after a delay in repressors. We suggest that repressors may reinterpret initially negative information in a more positive light after a delay, and therefore no longer experience the need to bias their recall after a delay.